NQR investigation of crystal structure peculiarities of layered Pbₓ₋₁Cdₓl₂ semiconductors - Gnatenko, Yu.P.; Beinik, I.A.; Barabash, A.I.; Vertegel, I.G.; Chesnokov, E.D.; Ovcharenko, A.I.; Ivanova, L.S. (Functional Materials, 2008)
The ¹²⁷l NQR spectra of semiconductor mixed crystals Pbₓ₋₁Cdₓl₂ at 77 K have been investigated. It is shown that at low values of Cdl₂ concentration, the intra-layer symmetry of the basic crystal becomes distorted considerably. This occurs due to formation of the intra-layer mechanical strains which are defined by the size difference between the main and impurity atoms (Pb and Cd, respectively). At x>0.10, intra-layer heterophasic two-dimensional Cdl₂ islets have been shown to be formed. The results are discussed that evidence the formation of amorphous glassy phase of the mixed Pbₓ₋₁Cdₓl₂ crystal at x>0.10.